Prenatal Attachment Relationship with Pregnant Women’s Compliance in Carrying Out Antenatal Care Visits - Mokoginta, Sri Venti; Dwiarini, Muafiqoh; Wijayanti, Indah; Lestari, Prasetya; Pham, Ngoc Thi (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2023)
Yogyakarta's 2022 health profile shows that MMR in 2021 is 580.34 from 2757 live births. Data from Basic Health Research (Riskesdas) conducted by the Ministry of Health of the Republic of Indonesia shows that 2017 K4 coverage nationally was 74.1%. This figure shows that mothers who receive the first visit do not continue the ANC according to the minimum standard of four visits. Antenatal care visits are an effort to reduce maternal and infant mortality. High maternal prenatal attachment is believed to be able to make a close emotional connection and encourage mothers to do positive things to improve their health. This study analyzed the relationship between prenatal attachment and pregnant women's compliance in the third-trimester antenatal care visit at Puskesmas Kasihan 1. The method used in this study is quantitative research with a cross-sectional approach. The sample used was 45 third-trimester pregnant women with uses purposive sampling technique. Data analysis using the Chi-Square Test. Chi-Square Test results obtain a p-value of 0.003 <0.05. This means that there is a significant relationship between prenatal attachment and the compliance of pregnant women with carrying out antenatal care. It can be concluded that there is a significant relationship between prenatal attachment and antenatal care compliance in pregnant women. A high level of prenatal attachment between mother and baby will affect the mother's compliance with antenatal care visits. The results of this study are expected to provide additional information to pregnant women about the importance of prenatal attachment in dealing with pregnancy.